Glycan–protein interactions determine kinetics of N-glycan remodeling. Issue 3 (19th April 2021) - Mathew, Corina; Weiß, R. Gregor; Giese, Christoph; Lin, Chia-wei; Losfeld, Marie-Estelle; Glockshuber, Rudi; Riniker, Sereina; Aebi, Markus
Abstract : Atomistic glycoprotein simulations reveal a site-specific availability of glycan substrates in time-resolved mass spectrometry of maturating enzyme kinetics. Abstract : A hallmark of N -linked glycosylation in the secretory compartments of eukaryotic cells is the sequential remodeling of an initially uniform oligosaccharide to a site-specific, heterogeneous ensemble of glycostructures on mature proteins. To understand site-specific processing, we used protein disulfide isomerase (PDI), a model protein with five glycosylation sites, for molecular dynamics (MD) simulations and compared the result to a biochemical in vitro analysis with four different glycan processing enzymes. As predicted by an analysis of the accessibility of the N -glycans for their processing enzymes derived from the MD simulations, N -glycans at different glycosylation sites showed different kinetic properties for the processing enzymes. In addition, altering the tertiary structure of the glycoprotein PDI affected its N -glycan remodeling in a site-specific way. We propose that the observed differential N -glycan reactivities depend on the surrounding protein tertiary structure and lead to different glycan structures in the same protein through kinetically controlled processing pathways.